Lives across cultures cross-cultural human development - Gardiner, Harry W. (Allyn and Bacon, 1998)
Appropriate as a supplement for a development course where a cross-cultural approach is emphasized in departments of Psychology and Anthropology. Provides a global and multicultural perspective to human development. Chapter topics are organized chronologically.